2018
DOI: 10.1136/bmjopen-2018-023636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic testing on low-density lipoprotein cholesterol in patients with familial hypercholesterolemia (GenTLe-FH): a randomised waiting list controlled open-label study protocol

Abstract: IntroductionFamilial hypercholesterolemia (FH) is an autosomal-dominant inherited genetic disease. High-throughput sequencing quickly and comprehensively detects causative variants of FH-related genes (LDLR, PCSK9, APOB and LDLRAP1). Although the presence of causative variants in FH-related genes correlates with future cardiovascular events, it remains unclear whether detection of causative gene mutation and disclosure of its associated cardiovascular risk affects outcomes in patients with FH. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…We are also now conducting another clinical trial (Impact of Genetic Testing on LDL Cholesterol in Patients with FH (GenTLe-FH)), which aims to assess the clinical benefits of genetic testing in FH subjects. 18 Our studies may provide interesting perspectives in returning genetic results with the disclosure of future ASCVD risk for patients with FH, and providing them with reliable and evidence-based treatment options to reduce their risk. We may associate our initiative in time with another Japanese FH registry, the PROLIPID-FH registry.…”
Section: Discussionmentioning
confidence: 96%
“…We are also now conducting another clinical trial (Impact of Genetic Testing on LDL Cholesterol in Patients with FH (GenTLe-FH)), which aims to assess the clinical benefits of genetic testing in FH subjects. 18 Our studies may provide interesting perspectives in returning genetic results with the disclosure of future ASCVD risk for patients with FH, and providing them with reliable and evidence-based treatment options to reduce their risk. We may associate our initiative in time with another Japanese FH registry, the PROLIPID-FH registry.…”
Section: Discussionmentioning
confidence: 96%
“…Such non-clinical consequences of genetic testing are labeled as patient empowerment ( 31 ). How genetic testing influences the individual's adherence to the given recommendations has been investigated among familial hypercholesterolemia patients ( 32 , 33 ), but no evidence is available for familial dysbetalipoproteinemia. It is of note, that women have another important risk factor for developing hypertriglyceridemia, over and above, unhealthy lifestyle habits.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have observed that hypercholesterolemia can cause multiple physiologic outcomes, such as coronary artery disease, diabetes and obesity [26, 27]. SOAT1 is an important protein for regulating cholesterol absorption and it plays a pivotal role in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%